2010
DOI: 10.1093/sleep/33.10.1396
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Modifications of the Upper Airway for Obstructive Sleep Apnea in Adults: A Systematic Review and Meta-Analysis

Abstract: A substantial portion of patients with obstructive sleep apnea (OSA) seek alternatives to positive airway pressure (PAP), the usual first-line treatment for the disorder. One option is upper airway surgery. As an adjunct to the American Academy of Sleep Medicine (AASM) Standards of Practice paper, we conducted a systematic review and meta-analysis of literature reporting outcomes following various upper airway surgeries for the treatment of OSA in adults, including maxillomandibular advancement (MMA), pharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
342
2
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(397 citation statements)
references
References 84 publications
10
342
2
23
Order By: Relevance
“…Palatal measurements form fundamental basis for orthodontic planning such as upper tooth extraction, maxillary dental implants, hemi-maxillectomy, orthognathic surgery, Le Fort fracture management, and cleft palate surgery [9]. Palatometry is also useful for preoperative evaluation of patients with uvulopalatopharyngoplasty [17].…”
Section: Discussionmentioning
confidence: 99%
“…Palatal measurements form fundamental basis for orthodontic planning such as upper tooth extraction, maxillary dental implants, hemi-maxillectomy, orthognathic surgery, Le Fort fracture management, and cleft palate surgery [9]. Palatometry is also useful for preoperative evaluation of patients with uvulopalatopharyngoplasty [17].…”
Section: Discussionmentioning
confidence: 99%
“…Success rates for isolated UPPP in the treatment of OSA are highly variable, depending on the size of the tonsils and the patient's body mass index [28]. Several variations of the technique have been proposed with similar outcomes [29]. UPPP has been also shown to be useful to lower CPAP pressure requirements, improving CPAP compliance in certain patients [30].…”
Section: Surgeries Of the Oropharynxmentioning
confidence: 99%
“…Several studies have shown that a MMA is equal in effectiveness to the nasal CPAP. MMA is the modality of surgery with the highest surgical efficacy and cure rate (43 %) [29,43].…”
Section: Craniofacial Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometry of the palate forms the fundamental basis for the treatment planning of orthodontic conditions such as orthognathic surgeries, maxillary dental implants, Hemi-maxillectomy, Le Fort fracture management, cleft palate surgery and also useful for preoperative evaluation of patients with uvulopalato pharyngoplasty [2,3]. The proper knowledge of the normal size and structure of this region is needed while performing some meticulous procedures such as Naso pharyngoscopy and nasogastric intubation and also needed for the better designing of instruments [4].…”
Section: Introductionmentioning
confidence: 99%